Could Mucosal TNF Transcript as a Biomarker Candidate Help Optimize Anti-TNF Biological Therapy in Patients With Ulcerative Colitis? - Cui, Guanglin; Florholmen, Jon; Goll, Rasmus (Frontiers in Immunology, 2022)
Anti-tumor necrosis factor (TNF) biological therapy has generally been accepted as a standard therapeutic option in inflammatory bowel disease (IBD) patient who are refractory to steroids or immunomodulators. However, the primary and secondary nonresponse rates to anti-TNF bioagents in patients with IBD are high. To improve the response rate, anti-TNF bioagents must be offered to the appropriate IBD patients, and the withdrawal of anti-TNF bioagents needs to be done at the right time. In this context, reliable and reproducible biomarkers can provide important supportive information for clinicians to make correct decisions based on the patient’s individual situation. In this review, we summarized the current understanding of using mucosal TNF transcript (TNF) to improve the precision of anti-TNF biological therapy strategies in patients with ulcerative colitis (UC). Analysis of published literature showed that mucosal TNF could affect the precision of the early identification of candidates who will benefit from anti-TNF therapy prior to treatment, the assessment of response and mucosal healing, and the prediction of discontinuation of anti-TNF biological therapy and relapse after drug withdrawal. Challenges and limitations of using mucosal TNF as a biomarker in applying individualized anti-TNF biological therapy in patients with UC still remain and need to be further investigated.